Cervical emphysema after tonsillectomy - Gómez-Torres, Antonio (2012)
Tonsillectomy, one of the most frequently surgery performed in otolaryngology, is a relatively safe surgical procedure. However, several complications have been described. We report a case of an adult patient with cervical emphysema after undergoing tonsillectomy, a rare complication. A deeper dissection creates a discontinuity that dissects the cervical planes and allows the air to reach the mediastinum and may cause a pneumothorax. Manoeuvres that increase the air pressure on the upper airway favour and increase the emphysema.